The Effect of Credit Development and Interest Income on Profits at Bank bjb - Agus Yudianto; Meddy Nurpratama (S1 Accounting Department, Faculty of Economic, Universitas Pamulang., 2022)
The economic activity of a country is inseparable from the traffic of money payments, where the banking industry plays a very strategic role, it can be said to be the lifeblood of the economic system, banks have the main function as an intermediary service with their main activities collecting funds from the public and channeling them back to the public and also as the center of a complex financial structure both nationally and internationally, where the objective is to support the implementation of national development. Identify problems that will be discussed further are as follows: How is the development of credit in 2012-2018 at bank bjb, How is the development of interest income in 2012-2018 at bank bjb, How is the development of profit in 2012-2018 at bank bjb, How is the influence of credit development on profits in 2012-2018 bank bjb, How is the influence of the development of interest income on profits in 2012-2018 at bank bjb. Given this problem to solve the problem between the effect of credit development and interest income on earnings, the researcher uses a simple regression coefficient